Passive tactile sensory input improves stability during standing - Rogers, Mark W.; Wardman, Daniel L.; Lord, Stephen R.; Fitzpatrick, Richard C. (Experimental brain research, 2001)
The effects of passive tactile cues about body sway on stability during standing were evaluated in subjects with a wide range of sensorimotor and balance performance. Healthy young adults, diabetic subjects with varying degrees of peripheral sensory neuropathy and older subjects aged 70-80 years were studied. Body sway was measured when subjects stood on the floor and on a foam rubber mat, with or without an applied stimulus that rubbed on the skin at the leg or shoulder as the body swayed. The results show that this stimulus reduced body sway (mean reduction 24.8%+/-1.5) and thus had a stabilizing effect as big as vision or sensory information from the feet. The reduction in sway was not based on active touch. The stimulus was not restricted to a particular region of the body, but was more effective on the shoulder than the leg, and was more effective when standing with eyes shut or when standing on the foam mat. It was also most effective in those subjects who had the greatest sway during normal standing. Thus, the response appears to be graded with the amplitude of the stimulus. We concluded that, if passive sensory input about posture is available, the postural control process adapts to this input, modulating postural stabilizing reactions.